Analysis of Students' Needs and Responses on The Development of Ethnoscience Integrated Vlog - Lestari, Indah Beti; Sudarmin, Sudarmin; Ellianawati, Ellianawati (Unnes Science Education Journal, 2021)
This research is the first stage to design, develop, implement and evaluate ethnoscience integrated Vlog learning media with the ADDIE model, namely the analysis stage. This research aims to analyze students' needs and responses if an ethnoscience integrated Vlog learning media is developed. The method used in this analytical research is a survey method using questionnaires and interviews. From the results of distributing questionnaires and also interviews, it is known that respondents were 215 students at MTs Al Uswah Bergas and a science teacher with a graduate educational background of S1-Science Education. From the data analysis results, it was found that students need media that can visualize material that is difficult to imagine by students and is contextual. Students are more enthusiastic, enthusiastic, and understand the material when using media such as video shows to clear the steps. The development of ethnoscience integrated Vlog learning media was welcomed by students with 58.6% of students needing ethnoscience integrated Vlog media, 24.7% very much need and 14% less need. Based on this data analysis, it can be concluded that this analytical research needs to be continued to the design, development, implementation and evaluation stages following the ADDIE model research and development procedure to develop ethnoscience integrated Vlog media in the context of science learning.